Implementasi Bauran Pemasaran Tabungan Easy Wadi’ah Pada Bank Syariah Indonesia - samsuki; Durrotun Nafisa (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2024)
The background of this research is the BSI Easy Wadi'ah savings provided by Bank Syariah Indonesia Darmahusada Surabaya. The research objectives in this study were: to find out the socialization strategy for BSI wadi'ah savings at Bank Syariah Indonesia KC DArmahusada. In conducting research the author uses a method that is descriptive qualitative. The data source of this research consists of primary and secondary data. As for the data collection techniques the authors use the method of documentation and observation and interviews. In conducting interviews, the authors chose 1 branch operation and service manager, and 1 customer service person as an informant because they have an important role in providing information. The results of this study indicate the socialization strategy for BSI Easy Wadi'ah savings at Bank Syariah Indonesia KC darmahusada which consists of 7Ps, namely: Product, Price, Place, Promotion, People, Process, Physical evidence.